An Experimental Study to Assess The Impact of Inorganic Additives on Water-Based Drilling Fluid Performance - ben mahmud, Hisham Khaled; Ayanarappan, Rugen; Shafiq, Mian Umer; Wang , Lei; Al-Fatlawi , Omar; Sadeq, Dhifaf (Testing Center for Oil and Gas LEMIGAS, 2026)
Drilling mud plays a crucial role in ensuring safe and cost-effective drilling operations, but it is often contaminated during the process and can significantly impact the mud's properties. Previous studies have largely addressed drilling mud contamination in a general sense, this work provides direct comparative insight into how sodium hydroxide (NaOH) alone and in combination with barite, lime, and calcium sulphate alters key rheological and physical properties of water-based muds (WBM) at a constant temperature of 25 °C. This paper investigates the effects of inorganic additives, specifically NaOH, on the properties of WBM. In this experimental study, six mud samples were prepared alongside a base mud, with three samples contaminated with varying concentrations of NaOH and the other three with different amounts of barite, lime, and calcium sulphate. The study focused on evaluating the rheological and physical properties of the mud at 25°C. The results showed that NaOH positively increased the mud alkalinity up to 12.75, but this was less pronounced as a result of the combinations with other additives like barite and calcium sulphate, reduced to 9.8. This trend is evident when higher NaOH concentrations result in increased fluid loss (≈ 40 ml at around 6 minutes) and decreased gel strength (≈ 13 lb/100 ft² after 10 minutes), which can negatively impact the mud's capacity to retain water and uphold structural integrity. However, the moderate doses of NaOH help in accelerating flocculation in the muds and increases the stability as well.